Теоретические и экспериментальные исследования сопротивляемости хрупким разрушениям сварных конструкций для шельфа Арктики - Горынин, И.В.; Ильин, А.В. (Автоматическая сварка, 2008)
Prevention of brittle fractures of welded structures of a shelf is an integrated problem, including the development of base and welding materials of high cold resistance, their certification by parameters of crack resistance and grounding of their applicability in the structure elements at a preset level of external effects on the basis of fracture mechanics approaches. To follow this path, it is necessary to solve a number of theoretical problems, connected with peculiarities of crack resistance tests of structurally non-homogeneous material of welded joints, interpretation of tests results, characterized by a large scattering, grounding of main principles of conductance of estimations. It is shown that the strength assurance by the criterion of prevention of brittle fractures requires not only the application of cold-resistant materials, but also optimizing of welding technology, updating of methods of non-destructive testing and criteria of assessment of quality of welds, as well as regulation of stress level in the structures.